Laser nano-filament explosion for enabling open-grating sensing in optical fibre - Keivan Mahmoud Aghdami (Nature Portfolio, 2021)
Engineered stop bands to sense an ambient environment can enable many applications. Here, the authors demonstrate well-controlled processes to open high-aspect ratio nanoholes through optical fibre for Bragg gratings in the telecomm spectrum and to enable high-resolution refractive index sensing